Experimental Investigation of the Vibration Behaviour of Variant GFRP Sandwich Panels in Thermal Environment - Philipp Hüttich; Emil Heyden; Dieter Krause (Polymer Testing)
In this study, the impact of temperature on the eigenfrequencies and amplifications of four variant GFRP sandwich panels with aramid honeycomb cores is investigated. Tests are carried out at temperatures from −40°C to 120°C, which are typical test conditions in the aerospace industry. The tests revealed that the eigenfrequencies of these panels are highly sensitive to temperature changes, with significant changes in vibration behaviour especially noted at temperatures below 0°C. Furthermore, the study shows that not all resonances develop most at room temperature. The specific dynamic properties and resulting resonances of the individual plates only develop under conditions of changing temperature. This finding is crucial for certification in aerospace and optimising structural design, ensuring robust performance across different operating conditions while leveraging the lightweight potential of the materials. The results highlight the complex interaction between temperature and dynamic behaviour in aerospace materials, providing essential data and insights for designing, analysing, and optimising lightweight aerospace structures. The aim of this publication is to provide initial investigations into the mechanisms behind the temperature-dependent dynamic responses in order to improve the prediction of larger structural components. This can be used in future developments to improve the safety, reliability and efficiency of aerospace systems.